2013
DOI: 10.1016/j.jep.2013.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary effects and disposition of luteolin and Artemisia afra extracts in isolated perfused lungs

Abstract: Ethnopharmacological relevance: Artemisia afra (Asteraceae) is a traditional medicinal plant frequently used in steam inhalation form to treat respiratory conditions. Aim of the study: Quantify luteolin content in Artemisia afra dried crude and aqueous extract. Evaluate the pulmonary effects of Artemisia afra steam inhalation, nebulized Artemisia afra extract and luteolin in isolated perfused lungs (IPL). Evaluate the pulmonary disposition of intravenously administered luteolin. Materials and methods: HPLC was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Species-specic compounds include for A. annua infusions some monoterpenes (e.g., linalool, limonene), sesquiterpenes (e.g., arteannuin B, dihydroartemisinic acid, possibly ART), avonoid aglycones (e.g., casticin, cirsilineol) and coumarins (e.g., esculetin, eleutheroside B1); for A. afra infusions only some monoterpenes (i.e., thujones and 6,7-epoxylinalool) as well as the avonoid aglycone quercetin, keeping in mind that the aqueous extracts of this species remain far less investigated than those of A. annua 26,30,61,62,94 and still await extensive analysis. 30,63,[111][112][113] Considering that the two species contain groups of similar metabolites, their infusions are likely to share a larger body of common compounds than the few ones detected up to now (i.e., camphor, eucalyptol, artemisia ketone, luteolin, cynaroside, several CGAs, scopoletin and scopolin). Plants most phytochemically similar to A. annua and A. afra are, as could be expected, other species within the very large Artemisia genus (>300 spp.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species-specic compounds include for A. annua infusions some monoterpenes (e.g., linalool, limonene), sesquiterpenes (e.g., arteannuin B, dihydroartemisinic acid, possibly ART), avonoid aglycones (e.g., casticin, cirsilineol) and coumarins (e.g., esculetin, eleutheroside B1); for A. afra infusions only some monoterpenes (i.e., thujones and 6,7-epoxylinalool) as well as the avonoid aglycone quercetin, keeping in mind that the aqueous extracts of this species remain far less investigated than those of A. annua 26,30,61,62,94 and still await extensive analysis. 30,63,[111][112][113] Considering that the two species contain groups of similar metabolites, their infusions are likely to share a larger body of common compounds than the few ones detected up to now (i.e., camphor, eucalyptol, artemisia ketone, luteolin, cynaroside, several CGAs, scopoletin and scopolin). Plants most phytochemically similar to A. annua and A. afra are, as could be expected, other species within the very large Artemisia genus (>300 spp.).…”
Section: Discussionmentioning
confidence: 99%
“…cynaroside). 30,62,63,[111][112][113][114] Infusions of A. annua show an important proportion of distinctive avonoids, minor as aglycones (e.g., eriodictyol, chrysosplenol D) and predominant as water-soluble heterosides (e.g., apigenin-6-C-b-D-glucoside, syn. isovitexin, quercetin-7-O-b-D-glucoside, syn.…”
Section: Flavonoidsmentioning
confidence: 99%
“…ex Willd. in isolated perfused lungs (Mjiqiza et al 2013). Both yarrow and sagebrush species also possess antibiotic activities (Maz et al 2013;Sarker et al 2007;Lopes-Lutz et al 2008;Obistioiu et al 2014) that may help protect against infections of the lungs (or other organs), and immunomodulatory effects that may help with symptoms of, and recovery from, infection as well as rheumatism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, antiallergic effect of luteolin was examined in mice and it was found that its administration reduced infiltration of inflammatory cells and decreased Th2 cytokines, thus exerting an antiallergic effect [ 119 ]. However, luteolin could also elicit a general improvement in lung function similar to those provided by bronchodilators [ 120 ].…”
Section: Preclinical Pharmacological Activities Of Luteolin: In Vivo Evidencementioning
confidence: 99%